PENGARUH PENGGUNAAN PERMAINAN RODA BERPUTAR UNTUK MENINGKATKAN KEMAMPUAN MENGENAL BANGUN DATAR ANAK TUNAGRAHITA RINGAN KELAS VII SMP DI SLBC - Krisma Febri Cahyaningtyas; Amelia Rizky Idhartono; Muhammad Nurrohman Jauhari (STRATEGY : Jurnal Inovasi Strategi dan Model Pembelajaran, 2026)
This study aimed to examine the effect of using a spinning wheel game as an instructional medium on the ability of students with mild intellectual disabilities in Grade VII at SLB C Pertiwi Ponorogo to recognize plane shapes. Students with mild intellectual disabilities experience difficulties in understanding the forms, names, and characteristics of plane figures due to cognitive limitations and low levels of abstract thinking; therefore, conventional teaching methods are considered less effective. Consequently, a spinning wheel game was employed as an interactive, play-based learning approach. The study used an experimental method with a pretest–posttest design. The participants consisted of four Grade VII students. Data were collected through tests measuring students’ ability to recognize plane shapes before and after the implementation of the spinning wheel game, and were analyzed using the sign test because the sample size was fewer than ten. The results showed a Z value of –1.27 at a significance level of 0.05, which was lower than the Z-table value of 1.96; thus, the hypothesis was accepted. The mean pretest score of 35 increased to 78 in the posttest. These findings indicate a significant improvement after the use of the spinning wheel game. Therefore, the spinning wheel game proved to have a positive and significant effect on improving the ability to recognize plane shapes among students with mild intellectual, disabilities and is recommended as an instructional medium in special education. ABSTRAK Penelitian ini bertujuan untuk mengetahui pengaruh penggunaan media permainan roda berputar terhadap kemampuan mengenal bangun datar pada anak tunagrahita ringan kelas VII di SLB C Pertiwi Ponorogo. Siswa tunagrahita ringan mengalami kesulitan dalam memahami bentuk, nama, dan karakteristik bangun datar karena keterbatasan kognitif serta rendahnya kemampuan berpikir abstrak, sehingga pembelajaran konvensional dinilai kurang efektif. Oleh karena itu, digunakan media permainan roda berputar sebagai pendekatan interaktif berbasis permainan. Penelitian menggunakan metode eksperimen dengan desain pretest–posttest. Subjek penelitian berjumlah empat siswa kelas VII. Data dikumpulkan melalui tes kemampuan mengenal bangun datar sebelum dan sesudah perlakuan, kemudian dianalisis menggunakan uji tanda karena jumlah sampel kurang dari sepuluh orang. Hasil analisis menunjukkan nilai Z sebesar –1,27 pada taraf signifikansi 0,05 yang lebih kecil daripada Z tabel 1,96, sehingga hipotesis diterima. Rata-rata skor pretest sebesar 35 meningkat menjadi 78 pada posttest. Temuan ini menunjukkan adanya peningkatan kemampuan yang signifikan setelah penggunaan media permainan roda berputar. Dengan demikian, media permainan roda berputar terbukti berpengaruh positif terhadap kemampuan mengenal bangun datar pada siswa tunagrahita ringan dan direkomendasikan sebagai media pembelajaran dalam pendidikan khusus.